1989
DOI: 10.1007/bf01788627
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the ecological distribution of the incidence of treated mental disorders in the city of Mannheim

Abstract: In 1965, Häfner et al. (1969) conducted an ecological study of the incidence of treated mental disorders in the industrial city of Mannheim. They found large variations in incidence rates in 20 urban areas: excess morbidity in the socially disorganized areas located mainly in the city center, and low rates in areas on the outskirts. This study incorporates additional data from the Cumulative Psychiatric Case Register established in Mannheim in 1973. It focuses on the short- and long-term stability of the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…In line with the earlier study by Hare (10) in Bristol, and in contrast to what was found in Nottingham (13,14) and Mannheim (15,16), later studies investigating the incidence of psychosis at the neighbourhood level reported at least some variation across neighbourhoods within cities (39,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Standardized incidence ratios of schizophrenia (57,59,60), non-affective psychosis (56) and all psychotic disorders (47) have been shown to vary considerably across neighbourhoods.…”
Section: Variation Across Neighbourhoodssupporting
confidence: 77%
See 3 more Smart Citations
“…In line with the earlier study by Hare (10) in Bristol, and in contrast to what was found in Nottingham (13,14) and Mannheim (15,16), later studies investigating the incidence of psychosis at the neighbourhood level reported at least some variation across neighbourhoods within cities (39,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Standardized incidence ratios of schizophrenia (57,59,60), non-affective psychosis (56) and all psychotic disorders (47) have been shown to vary considerably across neighbourhoods.…”
Section: Variation Across Neighbourhoodssupporting
confidence: 77%
“…Subsequent studies carried out in Nottingham (13,14) and Mannheim (15,16) also reported that rates of schizophrenia, but not affective psychosis, were elevated in inner-urban areas. However, in contrast to Hare (12), they found only limited variation within these areas across neighbourhoods.…”
Section: Geographical Variation In Incidencementioning
confidence: 95%
See 2 more Smart Citations
“…In two German studies results showed the impact of high density of population, increasing urbanization and less socially organizing on incidence and severity of schizophrenia (9,10). In another study, it was showed that the place of birth and the level of urbanization of the place one lived during the start of the illness increased the risk of schizophrenia for adults (11). Even though the result of this study suggests that internal migration does not affect the onset of schizophrenia, the number of studies on this issue is not satisfactory yet.…”
mentioning
confidence: 99%